A glucan from active dry baker’s yeast (Saccharomyces cerevisiae): A chemical and enzymatic investigation of the structure - Zlatković Dragan (Journal of the Serbian Chemical Society, 2003)
The structure of a polysaccharide consisting of D-glucose isolated from the cell-wall of active dry baker’s yeast (Saccharomyces cerevisiae) was investigated by using methylation analysis, periodate oxidation, mass spectrometry, NMR spectroscopy, and enzymic hydrolysis, as a new approach in determination of structures. The main structural feature of the polysaccharide deduced on the basis of the obtained results is a linear chain of (1→3)-linked β-D-glucopyranoses, a part of which is substituted through the positions O-6. The side units or groups are either a single D-glucopyranose or (1→3)-β-oligoglucosides, linked to the main chaing through (1→6)-glucosidic linkages. The low optical rotation as well as the 13C-NMR and FTIR spectra suggest that the glycosidic linkages are in the β-D-configuration.